2017
DOI: 10.1016/j.bmcl.2017.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Hsp90 inhibitors as antibiotics targeting histidine kinases

Abstract: To address the growing need for new antimicrobial agents, we explored whether inhibition of bacterial signaling machinery could inhibit bacterial growth. Because bacteria rely on two-component signaling systems to respond to environmental changes, and because these systems are both highly conserved and mediated by histidine kinases, inhibiting histidine kinases may provide broad spectrum antimicrobial activity. The histidine kinase ATP binding domain is conserved with the ATPase domain of eukaryotic Hsp90 mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 79 publications
0
21
0
1
Order By: Relevance
“…The bifunctional histidine kinase/phosphatase CckA controls the phosphorylation state of CtrA (69). CckA uses sensory PAS domains to change its activity depending upon its subcellular location and the progression of the cell cycle (10, 11).…”
Section: Introductionmentioning
confidence: 99%
“…The bifunctional histidine kinase/phosphatase CckA controls the phosphorylation state of CtrA (69). CckA uses sensory PAS domains to change its activity depending upon its subcellular location and the progression of the cell cycle (10, 11).…”
Section: Introductionmentioning
confidence: 99%
“…After identifying radicicol (7, Figure 2) as a putative binder, they used crystallography to confirm the interaction and determine that the aromatic ring of radicicol binds in similar orientations in Hsp90 and PhoQ, further supporting their initial hypothesis. A similar study was conducted by Vo et al (2017) using purified C-terminal domain of CckA from Caulobacter crescentus in a differential scanning fluorimetry assay In a screen of six commercially available Hsp90 inhibitors, NVP-AUY922 (8, Figure 2) and CCT018159 (9, Figure 2) were found to increase the melting temperature of CckA greater than 1.5°C relative to the control, indicating that they were able to tightly bind the C-terminal domain of CckA. Further studies revealed that these structurally similar inhibitors were also capable of inhibiting CckA activity in vitro.…”
Section: Pseudomonas Aeruginosamentioning
confidence: 73%
“…CckA (Vo et al, 2017) Signal transduction to control proteolysis regulation 8 (Vo et al, 2017), 9 (Vo et al, 2017) CheA (Stock et al, 1988) Chemotaxis 20 (Goswami et al, 2018), 21 (Goswami et al, 2018) DevS DosS (Converse et al, 2009;Gautam et al, 2015;Leistikow et al, 2010;Zheng et al, 2017) Oxygen sensing and surviving hypoxia 34 (Zheng et al, 2017), 35 (Zheng et al, 2017) EnvZ (Gilmour et al, 2005) Responding to changes in osmolarity; necessary for survival in macrophages 6 (Gilmour et al, 2005) KinA (LeDeaux et al, 1995) Regulates sporulation 1 (Barrett et al, 1998), 2 (Macielag et al, 1998) NblS (Waasbergen et al, 2002) Controls photosynthesis and photobleaching 14 (Velikova et al, 2016), 15 (Velikova et al, 2016) PhoR Phosphorus acquisition 16-18 (Velikova et al, 2016) YycG/WalK (Dubrac et al, 2007(Dubrac et al, , 2008Gilmour et al, 2005;Hancock & Perego, 2002;Lange et al, 1999;Martin et al, 1999;Okada et al, 2010;Watanabe et al, 2012) Signal transduction in cell wall signaling 6 (Gilmour et al, 2005), 10 (Okada et al, 2010, 11 (Watanabe et al, 2012), 12 (Igarashi et al, 2013), 13 (Huang et al, 2012;Qin et al, 2006Qin et al, , 2007, 14-17 (Velikova et al, 2016)…”
Section: Bacterial Survival and Fitnessmentioning
confidence: 99%
“…Cells with CckA FRET sensor expressed were incubated with the compound for 3 h. DMSO and Kanamycin were used as controls that should not impact the CckA FRET sensor. CCT018159 (IC 50 30 μM), CDV008 (IC 50 17.5 μM), and CDV009 (IC 50 12.5 μM) were previously shown to bind CckA in vitro …”
Section: Resultsmentioning
confidence: 96%